Gene Therapy to Treat Osteopenia Associated With Chronic Ethanol Consumption and Aldehyde Dehydrogenase 2 Deficiency - Anna E Camilleri; Michelle Cung; Fiona M Hart; Odelya E Pagovich; Ronald G Crystal; Matthew B Greenblatt; Katie M Stiles (JBMR Plus, 2023)
ABSTRACT Aldehyde dehydrogenase 2 (ALDH2) deficiency affects 35% to 45% of East Asians and 8% of the world population. ALDH2 is the second enzyme in the ethanol metabolism pathway. The common genetic variant ALDH2*2 allele has a glutamic acid‐to‐lysine substitution at position 487 (E487K) that reduces the enzyme activity, resulting in an accumulation of acetaldehyde after ethanol consumption. The ALDH2*2 allele is associated with increased risk of osteoporosis and hip fracture. Our prior study showed that administration of an adeno‐associated virus (AAV) serotype rh.10 gene transfer vector expressing the human ALDH2 cDNA (AAVrh.10hALDH2) before initiation of ethanol consumption prevented bone loss in ALDH2‐deficient homozygous knockin mice carrying the E487K mutation (Aldh2E487K+/+). We hypothesized that AAVrh.10hALDH2 administration after establishment of osteopenia would be able to reverse bone loss due to ALDH2 deficiency and chronic ethanol consumption. To test this hypothesis, male and female Aldh2E487K+/+ mice (n = 6) were given ethanol in the drinking water for 6 weeks to establish osteopenia and then administered AAVrh.10hALDH2 (1011 genome copies). Mice were evaluated for an additional 12 weeks. AAVrh.10hALDH2 administration after osteopenia was established corrected weight loss and locomotion phenotypes and, importantly, increased midshaft femur cortical bone thickness, the most important component of bone in the resistance to fractures, and showed a trend toward increased trabecular bone volume. AAVrh.10hALDH2 is a promising therapeutic for osteoporosis in ALDH2‐deficient individuals. © 2023 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.